Designing an E-Commerce Platform for Sibgah Boutique - Nur Syafika Rusman; Andi Ruslan; Syamsu Alam (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
The rapid advancement of information technology has accelerated digital transformation across various business sectors, including Micro, Small, and Medium Enterprises (MSMEs). Despite the widespread adoption of digital marketplaces, many MSMEs continue to face challenges related to high transaction fees, limited ownership of customer data, and dependence on third-party platforms, which may reduce long-term business profitability and sustainability. Therefore, developing an independent e-commerce platform has become a strategic alternative to strengthen business competitiveness and improve operational efficiency. This study aims to design, develop, and evaluate a website-based e-commerce platform for Sibgah Boutique using the Rapid Application Development (RAD) approach as a digital transformation strategy. The research employed a Research and Development (R&D) methodology consisting of planning, design, development, implementation, and evaluation stages. Data were collected through observation, interviews, documentation, and usability testing using the USE Questionnaire involving boutique owners, employees, and customers. Furthermore, the economic feasibility of the developed system was assessed through Cost–Benefit Analysis (CBA). The findings indicate that the developed platform successfully facilitates product management, inventory monitoring, and online transaction processing while reducing dependence on third-party marketplaces. The usability evaluation demonstrates that the system falls within the "Very Useful" category, indicating a high level of user acceptance and satisfaction. Moreover, the CBA results reveal that the projected economic benefits exceed the development costs, confirming the financial feasibility of the platform. The integration of usability evaluation and economic analysis provides a comprehensive assessment of the system's effectiveness in supporting MSME digital transformation. These findings reinforce the importance of independent e-commerce platforms in enhancing operational performance, increasing customer engagement, improving business profitability, and promoting sustainable digital business development.